In silico identification and characterisation of pathogenic genetic variants (nsSNPs) in the eukaryotic initiation factors eIF2 and eIF2B affecting miRNA binding sites - Pavan K. Madasu; V. Lokesh Subrahmanyam; Thyageshwar Chandran (Egyptian Journal of Medical Human Genetics)
Abstract Background The eukaryotic translation initiation factors (eIF2 and eIF2B) are known to play a regulatory role in translation initiation. Studies have indicated that several missense mutations in both eIF2 and eIF2B subunits can lead to severe neurological diseases and cancer. In the current study, we have attempted to identify and characterise the single-nucleotide polymorphisms (SNPs) in the said subunits and their correlation with various diseases. Results Interestingly, we could identify SNPs only in 3′ untranslated regions (3′UTR) from EIF2 (EIF2S1 and S3) and EIF2B (EIF2B1, B2 and B5 subunits). Of which, two SNPs, one in each EIF2B1 (rs1050448) and EIF2B2 (rs4556), are observed to be affecting miRNA binding sites. The gene ontology (GO) analysis of identified miRNAs indicates their association with central nervous system development, various stress responses, growth factors, and immune system signalling pathways. Furthermore, molecular docking studies also confirm that the identified miRNAs have an excellent binding ability with corresponding wild-type/mutant dsDNA and mRNA with HADDOCK binding scores in the range of − 38.78 to − 3.99 kcal/mol and − 86.47 to − 23.78 kcal/mol, respectively. Conclusion We conclude that the identified miRNAs may play a regulatory role in the symptomatic progression of neurological disorders and cancer and the same is validated by existing experimental evidences. Overall, the identified miRNAs serve as potential candidates for carrying out clinical investigations. Graphical abstract